HUMAN FIGURE DRAWING CONTRIBUTIONS FOR BODY IMAGE ASSESSMENT IN ANOREXIA NERVOSA - Peres, Rodrigo Sanches; Santos, Manoel Antônio (Medicina (Ribeirao Preto), 2006)
The present study was developed to evaluate the body image of anorexia nervosa patients. The Human Figure Drawing (HFD) was used as instrument, because is a graphic projective technique that makes possible the investigation of the deep psychological processes and the mental representation of himself. A number of 10 anorexic women treated at Grupo de Assistência em Transtornos Alimentares (GRATA) from HC-FMRP-USP were assessed. The collected material was evaluated in accordance with the procedures described at the scientific literature. The results indicate that part of the appraised women presents a negative body image, permeated clearly by inferiority, inadequacy, and insecurity feelings. However, some participants projected in the drawings an idealized body image, influenced directly by compensatory mechanisms of defense. Such results indicate that HFD can be considered a useful technique for body image evaluation in anorexia nervosa and a valuable alternative to the psychometrics instruments usually employed with this purpose.